Beautiful, complicated—and intelligent? Novel aspects of the thigmonastic stamen movement in Loasaceae - Henning, Tilo (Landes Bioscience, 2013)
In a recent study we investigated the complex mechanisms regulating the pollen release via thigmonastic stamen movement found exclusively in Loasaceae subfamily Loasoideae. We demonstrated that stamen movement is modulated by abiotic (light and temperature) as well as biotic stimuli (pollinator availability and visitation frequency). This is explained as a mechanism to adjust the rate of stamen movement and thus pollen dispensation to different environmental conditions in order to optimize pollen transfer. Stamen movement is rapid and thus a near-immediate response to pollinator visits. However, Loasaceae flowers also show a response to biotic stimuli on a longer time scale, by adjusting the duration of both the staminate and the carpellate phase of the anthesis. We here present two additional data sets on species not previously studied, underscoring the shortening of the staminate phase in the presence of pollinator visits vs. their absence and the shortening of the carpellate phase after pollination. Overall, the plant shows not only a rapid but an “intelligent” reaction to its environment in adjusting anthesis and pollen presentation to a range of factors. The physiological and morphological bases of the stamen movement are poorly understood. Our previous study showed that there is no direct spatial relationship between the place of stimulation in the flower and the stamen bundle activated. We here further show the morphological basis for stamen movement from a reflexed into an erect position: Only the basal part of the filament curves around the receptacle, while the upper part of the filament retains its shape. We hypothesize that the stimulus is transmitted over the entire receptacle and the place of reaction is determined by stamen maturity, not the location of the stimulus.